2021
DOI: 10.1002/jcsm.12789
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength and muscle mass as predictors of hospital length of stay in patients with moderate to severe COVID‐19: a prospective observational study

Abstract: Background Strength and muscle mass are predictors of relevant clinical outcomes in critically ill patients, but in hospitalized patients with COVID‐19, it remains to be determined. In this prospective observational study, we investigated whether muscle strength or muscle mass are predictive of hospital length of stay (LOS) in patients with moderate to severe COVID‐19 patients. Methods We evaluated prospectively 196 patients at hospital admission for muscle mass and strength. Ten patients did not test positive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 26 publications
4
74
0
Order By: Relevance
“…In critically-ill septic patients, Cox Mc et al, reported a prevalence of baseline low muscle mass in 50% of patients [39]. Another study in hospitalized patients with COVID-19 showed that muscle mass was related to the need for ICU admission (17%), longer hospital LOS (mean, 10.8 days), and mortality (6.6%) [40]. Although their results are not comparable to our population of critically ill patients as muscle mass was assessed using ultrasound, their findings corroborate with ours by highlighting low muscle mass as an independent predictor of negative clinical outcomes [37], including higher rates of extubation failure, defined as reintubation within 48 hours after extubation following long-term MV for >7 days [41].…”
Section: Discussionmentioning
confidence: 99%
“…In critically-ill septic patients, Cox Mc et al, reported a prevalence of baseline low muscle mass in 50% of patients [39]. Another study in hospitalized patients with COVID-19 showed that muscle mass was related to the need for ICU admission (17%), longer hospital LOS (mean, 10.8 days), and mortality (6.6%) [40]. Although their results are not comparable to our population of critically ill patients as muscle mass was assessed using ultrasound, their findings corroborate with ours by highlighting low muscle mass as an independent predictor of negative clinical outcomes [37], including higher rates of extubation failure, defined as reintubation within 48 hours after extubation following long-term MV for >7 days [41].…”
Section: Discussionmentioning
confidence: 99%
“…The authors were contacted to clarify any doubts about the articles. Unpublished data were requested, however, only the assessment of number of deaths caused by COVID-19 was used to perform the analysis ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Gil et al assessed 196 hospitalized patients for vastus lateralis cross-sectional area using ultrasonography and concluded that low muscle mass contributes to higher skeleton muscle loss among COVID-19 patients due to increased demands of tissues such as liver and immune cells [90]. Those patients with weak muscle strength are more vulnerable to stress factors, which could be the case of COVID-19 [91,92]. Other studies have found that with COVID-19 treatment, 43% of study participants lost ≥5% of their body weight, and 25% of participants lost ≥10% of their body weight.…”
Section: Sars-cov-2 (Covid-19) Induced Cytokine Storm In Muscle Wasti...mentioning
confidence: 99%